Cardiac output changes from prior to pregnancy to post partum using two non-invasive techniques. Issue 9 (30th October 2018) - Masini, Giulia; Foo, Lin F; Cornette, Jérôme; Tay, Jasmine; Rizopoulos, Dimitris; McEniery, Carmel M; Wilkinson, Ian B; Lees, Christoph C
Abstract : Objectives: We aimed to describe cardiac output (CO) trend from prepregnancy to post partum using an inert gas rebreathing (IGR) device and compare these measurements with those obtained by a pulse waveform analysis (PWA) technique, both cross-sectionally and longitudinally. Methods: Non-smoking healthy women, aged 18–44 years, with body mass index <35 were included in this prospective observational study. CO measurements were collected at different time points (prepregnancy, at four different gestational epochs and post partum) using IGR and PWA. A linear mixed model analysis tested whether the longitudinal change in CO differed between the techniques. Bland-Altman analysis and intraclass correlation coefficient (ICC) were used for cross-sectional and a four-quadrant plot for longitudinal comparisons. Results: Of the 413 participants, 69 had a complete longitudinal assessment throughout pregnancy. In this latter cohort, the maximum CO rise was seen at 15.2 weeks with IGR (+17.5% from prepregnancy) and at 10.4 weeks with PWA (+7.7% from prepregnancy). Trends differed significantly (p=0.0093). Cross-sectional analysis was performed in the whole population of 413 women: the mean CO was 6.14 L/min and 6.38 L/min for PWA and IGR, respectively, the percentage of error was 46% and the ICC was 0.348, with similar results at all separate time points. Longitudinal concordance was 64%. Conclusions: Despite differences between devices, the maximum CO rise in healthy pregnancies is more modest and earlier than previously reported. The two methods of CO measurement do not agree closely and cannot be used interchangeably. Technique-specific reference ranges are needed before they can be applied in research and clinical settings.